Influence of Artificial Intelligence in Human Resource Management: A Comprehensive Review - Nikita Saklani; Ashli Khurana (International Journal of Engineering and Management Research, 2023)
In the current competitive environment, precise data collection and analysis are critical for many professional divisions to ensure smooth daily operations. Artificial intelligence (AI), which includes subfields like machine learning, makes it possible for industries to work quickly and efficiently in a field of computer science that mimics the thought processes of humans. In human resources, AI tools can automate routine tasks, allowing employees to focus on more strategic and engaging work, including subfields like machine learning, and making it possible for industries to work quickly and efficiently. Adopting cutting-edge technology within an organization is crucial for effectively deploying AI due to increasing business pressures. Even demanding bosses recognize the value of AI in the workplace. This paper explores the impact of AI on human resources.